Transfer of maternal immunity using a polyvalent vaccine and offspring protection in Nile tilapia, Oreochromis niloticus [version 4; peer review: 1 approved, 2 approved with reservations] - Wahidah Wahidah; Amrullah Amrullah; Indrayani Indrayani; Ardiansyah Ardiansyah (F1000Research, 2023)
Background Vaccination is an effective and alternative means of disease prevention, however, it cannot be conducted on the offspring of fish. For this process to take place, the transfer of maternal immunity should be implemented. This study aims to determine the effectiveness of transferring immunity from the broodstock to the offspring using a polyvalent vaccine against Aeromonas hydrophila, Streptococcus agalactiae, and Pseudomonas fluorescens in Nile tilapia, Oreochromis niloticus. Methods Nile tilapia broodstock with an average weight of 203g (±SD 23) was reared in spawning ponds until mass spawning and harvested one week post-spawning for vaccination. After being vaccinated according to the treatment, each fish broodstock was reared in 3x3 m cages installed in an earthen pond with a density of 20 broodstock, consisting of 15 females and 5 males. The vaccine used was a formalin-killed whole-cell vaccine at a density of 1010 cfu/mL injected intramuscularly (i.m.) at a dose of 0.4 mL/kg fish. Nile tilapia was injected with a vaccine used as a treatment. Example include A. hydrophila monovalent (MA), S. agalactiae monovalent (MS), P. fluorescens monovalent (MP), A. hydrophila and S. agalactiae bivalent (BAS), A. hydrophila and P. fluorescens bivalent (BAP), P. fluorescens and S. agalactiae bivalent (BPS), and A. hydrophila, S. agalactiae, and P. fluorescens polyvalent vaccines (PAPS). While the control was fish that were injected with a PBS solution. The broodstock’s immune response was observed on the 7th, 14th, 21st, and 28th days, while the immune response and challenge test on the offspring was conducted on the 10th, 20th, 30th, and 40th day during the post-hatching period. The parameters observed consisted of total leukocytes, phagocytic activity, antibody titer, lysozyme, and relative survival percentage (RPS). Result The application of PAPS in broodstock could significantly induce the best immune response and immunity to multiple diseases compared to other treatments. The RPS of the PAPS was also higher than the other types of vaccines. This showed that the transfer of immunity from the broodstock to the Nile tilapia offspring could protect it against bacterial diseases such as A. hydrophila, S. agalactiae, and P. fluorescens. Conclusion The application of polyvalent vaccine A. hydrophila, S. agalactiae, P. fluorescens vaccines increased the broodstock’s immune response and it was transferred to their offsprings. Polyvalent vaccines derived from maternal immunity can protect offspring from disease up to 30 days of age. They were able to produce tilapia seeds that are immune to diseases caused by A. hydrophila, S. agalactiae, and P. fluorescens.